Symbolic Violence in Indonesian Society: Islamic Radicalisation Leads to Religious Intolerance? - Irfan Latifulloh Sarhindi (Journal of Southeast Asian Human Rights, 2017)
In terms of religions, Islam shares too big the percentage of Indonesia’s population as it becomes the biggest Muslim majority country. Inevitably, Islam dominates the rule of conduct of the society. Subsequently, Indonesian Muslims seem to enjoy privileges while social hierarchy is normalized. Such a situation marks the existence of symbolic violence in Indonesian society. This would not be exacerbated unless the hegemon ignores, or even does harm to, the voice of the marginal. This would alarm the religious tolerance. Sadly, this appears to be the case given the rise of Islamic conservativism and radicalisation in post-1998 Indonesia. With their closed-mindedness, self-righteousness, and judgmental attitude in one hand, and power and homogeneity on the other, one single religious sentiment can fall into a damaged social friction. Hence, hatred appears to be cultivated. Drawing on this line, widening perspective and mind set, as well as strengthening inter-group and inter-religion dialogues would be beneficial.